2000
DOI: 10.1038/sj.jhh.1000944
|View full text |Cite
|
Sign up to set email alerts
|

The 460Trp polymorphism of the human α-adducin gene is not associated with isolated systolic hypertension in elderly Australian Caucasians

Abstract: The study was undertaken to determine whether polymorphic variants of the ␣-adducin gene are associated with isolated systolic hypertension (ISH) in elderly Australian Caucasians. Participants were classified with ISH (n ‫؍‬ 87, systolic blood pressure (SBP) у160 mm Hg and diastolic blood pressure (DBP) р90 mm Hg) or normotension (n ‫؍‬ 124, SBP Ͻ140 mm Hg and DBP Ͻ90 mm Hg with no family history of hypertension). To collect demographic data, a structured questionnaire was used. DNA was extracted using standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(24 reference statements)
1
9
1
Order By: Relevance
“…Further, we also analyzed the association between ADD1 Gly460Trp polymorphism and essential hypertension by combining 15 case-control studies, involving 3187 cases and 3720 controls[913222427] as shown in Table 4. Surprisingly, the overall prevalence of 460Trp allele was higher in control subjects that amounted to 34.7% as compared to 32% in cases.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we also analyzed the association between ADD1 Gly460Trp polymorphism and essential hypertension by combining 15 case-control studies, involving 3187 cases and 3720 controls[913222427] as shown in Table 4. Surprisingly, the overall prevalence of 460Trp allele was higher in control subjects that amounted to 34.7% as compared to 32% in cases.…”
Section: Resultsmentioning
confidence: 99%
“…Population-based and hospital-based studies were all included in our meta-analysis. Twelve studies were population-based [9], [13], [20], [22], [23], [25][28], [30][32], and ten were hospital-based studies [6][8], [10][12], [21], [24], [29], [33]. Populations among these studies were as following: ten studies were Caucasians or European descent (7632 cases and 8588 controls), nine studies were East Asians (5957 cases and 6770 controls) and three studies were others (one study recruited South African Negro subjects and the other two studies recruited African-American subjects) involving 714 cases and 603 controls.…”
Section: Resultsmentioning
confidence: 99%
“…In 10 populations, a positive association was found (10,13,32,42,80,116,119,124,156), whereas in two populations, a positive association was found only in women (128) or young subjects (132). In 13 populations, no association was present (2,3,38,70,74,79,84,88,100,116,119,124,151). In three studies (116,119,124), both positive and negative associations are observed in different populations.…”
Section: Studies In Humansmentioning
confidence: 86%